The novel protein KBP regulates mitochondria localization by interaction with a kinesin-like protein - Dorner Cornelia (BMC Cell Biology, 2005)
Abstract Background Members of the Kinesin-3 family of kinesin-like proteins mediate transport of axonal vesicles (KIF1A, KIF1Bβ), distribution of mitochondria (KIF1Bα) and anterograde Golgi to ER vesicle transport (KIF1C). Until now, little is known about the regulation of kinesin-like proteins. Several proteins interact with members of this protein family. Here we report on a novel, KIF1 binding protein (KBP) that was identified in yeast two-hybrid screens. Results KBP was identified by using the yeast-two-hybrid system with an amino-terminal fragment of KIF1C as a bait that is strongly homologous to KIF1B. Here we investigated the interaction of KBP and KIF1B. The full length proteins coimmunoprecipitated after overexpression and in untransfected 293 cells. Immunofluorescence experiments revealed that KBP was mainly localized to mitochondria, as has been described for KIF1Bα. Overexpression of a deletion mutant or reduction of the KBP protein level using an anti-sense construct led to an aggregation of mitochondria. Such an effect is probably due to the lower activity of KIF1Bα in the absence of KBP, as was revealed in motility assays. Conclusion KBP is a new binding partner for KIF1Bα that is a regulator of its transport function and thus represents a new type of kinesin interacting protein.